Organic additive release from plastic to seawater is lower under deep-sea conditions - Vincent Fauvelle (Nature Portfolio, 2021)
Plastics are major marine pollutants, and while research suggests that they can release potential harmful additives into seawater, how environmental conditions influence this is unknown. Here the authors determine that byproducts released from microplastics are less under deep-sea conditions versus surface.